Randomised controlled trial on the effect of simethicone bowel preparation on rectal variability during image‐guided radiation therapy for prostate cancer (SPoRT study). Issue 6 (24th March 2022) - Ward, Jennifer; Gill, Suki; Armstrong, Kevin; Fogarty, Tamara; Tan, Daren; Scott, Alison; Yahya, Aylin; Dhaliwal, Satvinder Singh; Jacques, Angela; Tang, Colin
Abstract: Introduction: The purpose of this study was to assess whether simethicone reduces the rectal volume (RV) and gas volume (GV), to increase treatment accuracy and to decrease toxicity of prostate radiation therapy. Methods: 30 patients were randomised to simethicone or no intervention. Cone‐beam computed tomography (CBCT) scans were performed on Days 1–3 and weekly until completion of radiation. RV and GV were measured using volume delineation. Toxicity data were collected. Results: 264 CBCTs were analysed. RV and GV were not significantly different in the simethicone group compared with the control group at each time point ( P >0.05) after adjusting for Week 0 values as a covariate. The simethicone group showed an average reduction in RV and GV of 10% and 21%, respectively, compared with the control group ( P >0.05). Standard deviations were calculated over 10 time points, which were grouped to represent the first 2–3 weeks of radiation therapy versus subsequent weeks. These were not significantly different between the simethicone and control group. However, there was a statistically significant decrease in the variability of RV at time points 6–10 compared with time points 1–5 within the simethicone group ( P = 0.012), but no significant difference was found between these grouped time points in the control group ( P = 0.581). The toxicity questionnaires showed no significant difference between the groups. Conclusions: Simethicone did not decrease the RV or GV overall. However, simethicone appeared to significantly decrease the RV variability from Week three onwards. This suggests that taking simethicone two to three weeks before starting radiation therapy may reduce RV variability, although a larger study is needed to confirm this.